PENGARUH PELATIHAN DAN INSENTIF TERHADAP KINERJA GURU DI SMA AR RISALAH LUBUKLINGGAU - Muchoyyarotu Millah Al Hadi; Noorhamid Ustadi (Jurnal Interprof, 2017)
Teacher performance is the result of work achieved by a teacher in carrying out its duties in accordance with the responsibilities given. Will based on the facts in the field, teacher performance is still not optimal. The purpose of this research is to know the big influence on teacher performance in SMA Ar Risalah Lubuklinggau either simultant or partially. This research is a saturated sample research that is on 30 teachers in Ar Risalah Lubuklinggau High School. Data method used is questionnaire method. Data analysis method used is descriptive and analysis. The result of descriptive research shows the average performance score of 59.60, the training variables in the medium category with the average score of 64.80, the incentive variable in the medium category with an average score of 67,. While based on statistics showing training and incentives contributed 41.99% to the performance of teachers in Ar Risalah Lubuklinggau High School. Suggestions that can be conveyed are teachers in SMA Ar Risalah Lubuklinggau need also improved training that support its performance, principal expected more attention all members of school with teacher value.